Preferensi Konsumen dan Analisis Titik Impas Pembuatan Kue Kembang Goyang - Ratna Wylis Arief; Yulia Pujiharti (Journal of Food System & Agribusiness, 2019)
Shake flower cookies is a type of traditional Indonesian cookies made from rice flour. Processing rice groats into rice groats flour and using it as a raw material for making shake flower cookies aims to increase the added value of rice groats which has only been used as animal feed. The research was conducted in Ponco Kresno Village, Negeri Katon Subdistrict, Pesawaran District, from September to December 2016. The treatment applied was the difference in the composition of flour used, namely: A = 100% Rose Brand rice flour ; B = rice groats flour 90% + tapioca flour 10%; C = rice groats flour 80% + tapioca flour 20%; and D = rice groats flour 100%. The results showed that treatment C (rice groats flour 80% + tapioca flour 20%) could be developed for entrepreneurial shake flower cookies, because statistically it did not show a significant difference in color, taste, crispness, and general acceptance compared to the use of rose brand rice flour 100%, and the capital needed is the lowest compared to other treatments, which is only Rp. 4,860, - / pack, while the price of the selling shake flower cookies on the market for all treatments is the same, Rp. 9,000, - / pack, so that the benefits obtained by farmers when using treatment C are higher than other treatments.